The star formation burstiness and ionizing efficiency of low-mass galaxies. Issue 3 (12th February 2022) - Atek, Hakim; Furtak, Lukas J; Oesch, Pascal; van Dokkum, Pieter; Reddy, Naveen; Contini, Thierry; Illingworth, Garth; Wilkins, Stephen
ABSTRACT: We investigate the burstiness of star formation and the ionizing efficiency of a large sample of galaxies at 0.7 < z < 1.5 using HST grism spectroscopy and deep ultraviolet (UV) imaging in the GOODS-N and GOODS-S fields. The star formation history (SFH) in these strong emission-line low-mass galaxies indicates an elevated star formation rate (SFR) based on the Hα emission line at a given stellar mass when compared to the standard main sequence. Moreover, when comparing the Hα and UV SFR indicators, we find that an excess in SFRHα compared to SFRUV is preferentially observed in lower mass galaxies below 10 9 M⊙, which are also the highest-EW galaxies. These findings suggest that the burstiness parameters of these strong emission-line galaxies may differ from those inferred from hydrodynamical simulations and previous observations. For instance, a larger burstiness duty cycle would explain the observed SFRHα excess. We also estimate the ionizing photon production efficiency ξion, finding a median value of log(ξion /erg −1 Hz) = 24.80 ± 0.26 when adopting a Galactic dust correction for Hα and an SMC one for the stellar component. We observe an increase of ξion with redshift, further confirming similar results at higher redshifts. We also find that ξion is strongly correlated with EWHα, which provides an approach for deriving ξion in early galaxies. We observe that lower mass, lower luminosity galaxies have a higher ξion . Overall, these results provide further support for faint galaxies playing a major role in the reionization of the Universe.